2020
DOI: 10.1177/2631787720969697
|View full text |Cite
|
Sign up to set email alerts
|

The Grand Challenge of Corporate Control: Opening strategy to the normative pressures of networked professionals

Abstract: We propose that the pre-eminent ‘grand challenge’ for organization theorists today is the societal control of powerful corporations. This grand challenge is the more urgent because of the contemporary inadequacies of markets, hierarchies and regulations as instruments of control. We argue for the potential role of ‘open strategy’ in mobilizing normative controls over big business. We develop a distinction between the managed and unmanaged practices of open strategy. Both can help expose corporations to normati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 74 publications
0
43
0
Order By: Relevance
“…Furthermore, with its interest in the distributed nature of strategy work, SAP research is in a particularly strong position to expose various informal and implicit governance mechanism, whereas corporate governance research to date has focused on the formal and explicit ones. An example of the kind of insights such work might offer is Whittington and Yakis-Douglas’ (2020: 3) explanation of how ‘unmanaged forms of openness’, such as unintended information leaks, together with the normative pressure of globally networked professionals, help control powerful organizations.…”
Section: Where Is Sap Heading? the Contours Of An Emerging New Phase ...mentioning
confidence: 99%
“…Furthermore, with its interest in the distributed nature of strategy work, SAP research is in a particularly strong position to expose various informal and implicit governance mechanism, whereas corporate governance research to date has focused on the formal and explicit ones. An example of the kind of insights such work might offer is Whittington and Yakis-Douglas’ (2020: 3) explanation of how ‘unmanaged forms of openness’, such as unintended information leaks, together with the normative pressure of globally networked professionals, help control powerful organizations.…”
Section: Where Is Sap Heading? the Contours Of An Emerging New Phase ...mentioning
confidence: 99%
“…Discussion and future research Scholars have been increasingly calling for greater attention to the problem of deterring CSI (Buckley, 2018a;Whittington and Yakis-Douglas, 2020). Some researchers have simplistically attributed CSI to MNE malevolence (Bakan, 2005), rather than emerging as a consequence of institutional complexity.…”
Section: Mbr 293mentioning
confidence: 99%
“…Accusations of irresponsible MNE behavior include the working conditions violations at the fashion brand Boohoo in the UK, the abuse of market power by Facebook in Australia, and very recently, the opioid crisis in the United States, which has, so far, led to several large multinational pharmaceutical companies -as well as the consulting giant McKinsey -settling litigation charges in connection with business malpractice which contributed to nearly 50,000 opioid overdose fatalities in the U.S. in 2019 (drugabuse.gov, 2021). Yet, despite the often complex, severe and urgent nature of CSI (Buckley et al, 2017;Whittington and Yakis-Douglas, 2020), IB research has mainly drawn on a set of implicit assumptions about the CSI construct, rather than developing a precise definition. Such assumptions concerning CSI have been predominantly informed by an international business (IB) policy perspective, which typically focuses on how instances of CSI can be detrimental to MNE performance; as institutions, through litigation and regulatory sanctions, are expected to 'step-in' to penalize MNEs following their irresponsible behavior (Buckley, 2018b;Buckley and Casson, 1976;Karpoff, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Massey, 2005, p. 11) The argument about openness/closure […] should not be posed in terms of abstract spatial forms but in terms of the social relations through which the spaces and that openness and closure are constructed […] (Massey, 2005, p. 165) Recent research has shown open strategy to be a multifaceted and highly dynamic phenomenon (Seidl, von Krogh, & Whittington, 2019) highlighting that openness in strategizing also entails closure (Dobusch, Dobusch, & Müller-Seitz, 2019). Focusing on the two dimensions of openness, namely transparency and inclusion (Hautz, Seidl, & Whittington, 2017;Whittington, Cailluet, & Yakis-Douglas, 2011) research has already examined the dynamics of openness in terms of who should be included or excluded in the strategy process at the organizational (Mack & Szulanski, 2017;Vaara, Rantakari, & Holstein, 2019) and inter-organizational level (Seidl & Werle, 2018); what kind of information should be shared and to what extent (Malhotra, Majchrzak, & Niemiec, 2017); and how openness can be promoted or impeded (Whittington & Yakis-Douglas, 2020). However, the question of 'where' has gained less attention and left the role of organizational space untheorized in open strategy research.…”
mentioning
confidence: 99%